Oferta Laboral en México: un enfoque de variables instrumentales - Caamal Olvera, Cinthya (Universidad Autónoma de Nuevo León, 2007)
The purpose of this paper is to estimate the labour supply in Mexico during the period 1988-2002, using micro information in a macro context. This objective will be pursued by analysing the factors relating to the decision of how many hours to work crosswise households, which is made by the head of household. This paper also examines whether or not macro factors, such as public spending on education made at the state level, might influence this decision across states. Firstly, the relevant demographic characteristics of heads of households, as well as assorted state decisions about education spending, are examined in order to estimate a labour supply and map the different responses from households across states.It is useful to estimate the wage elasticity in order to account for the factors that make people work more hours and observe whether there is a preference for work or leisure and how spending on education, and the resulting wage effects, makes people modify their choices. There are several factors that influence the endogenous relationship between hours of work and wages; that is, the decision to work is affected by regional differences, limited number of vacancies across states, lack of unemployment benefits and reduced benefits received from government.The Mexican case is interesting not only because of the differences in wage, education and development across states but also because of the tendency to work more hours per week than several developed countries on a regular annual base. For example, during the period of time considered and based only on working people aged 20-55 years old, one observes that men work on average 481 hours while women work about 38 hours per week. Alesina and Glaeser (2005) compare the hours worked by those employed and at working age in Europe and United States. They note that the US has the highest value for working hours, which is 392, while the lowest is Italy with